TINDAK PIDANA TERHADAP KEAMANAN NEGARA DALAM PERSPEKTIF DELIK POLITIK DI INDONESIA - Siahaan, Hotman (Solusi, 2018)
In determining an actor crime as a political offense we have to look at the background of these actions. The problem, however, related with the codification such as the Criminal Code. It does not expressly provide the identification the action in the field of politics. In the Criminal Code, for example, the murder of president or vice president, did not be regarded as the murder. That is, evidence about the political background is not necessary to have the trial court. While the law relating to this problem such Act. 11/PNPS/1963 on Combating Subversive Activities that have been revoked, have two opinions. First, states have no political background. Second, there should be no political background. The fundamental difference of these two opinions is about an act as a political offense,one side assumes the other party would destroy the existing system, on the other hand is considered an act of rescue (hero).